STUDY OF DEVELOPMENT TRADITIONAL FISH LANDING PLACE BAGAN HULU VILLAGES, SUBDISTRICT OF BANGKO, DISTRICT OF ROKAN HILIR PROVINCE OF RIAU - Mela Sari; Ronald Mangasi Hutauruk; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Mostof Bagan Hulu residents work as fisher. However, state fish landing place is still not exist in the area. To understand facility condition, fishing fleet, fishing units, activity and possibility to develop fish landing place in Bagan Hulu village, the research was conducted by using method survey. The results shows Bagan Hulu has two traditional fish landing places A (TPI A) and B (TPI B), managed by self-owned businesses. Both fish landing place is very simply. Types of machine of vessel are Mitsubischi and Dompeng the dimension of vessel that landing their fish hold to TPI 10-20 m long, 1-2 m wide, and 1-2 m draf. Fishing gear used are anchoring and filling the supplies. SWOT result shows TPI A is in the firs quadrant that mean the condition is provitable, mean while TPI B is in the for the quadrant that mean facing major challenges recommendation strategy survive.Keywords: Bagan Hulu, Mediator, SWOT